Liquefied natural gas - Abdul Majid, Zulkifli (Faculty of Chemical & Natural Resources Engineering, 1992)
For many years, natural gas was regarded as useless by-product of crude oil production and flared or vented in vast quantities. Gradually, however, it began to replace town gas, manufactured mainly from coal, as its superior qualities as a clean burning, efficient fuel were realized. Following the growth of the gas industry in North America, natural gas found increasing use in Europe after the discovery of substantial non-associated gas fields close to potential markets.